Clinical cases in eye care - Rosenfield, Mark; Lee, Eunice Myung; Goodwin, Denise (Wolters Kluwer, 2019)
"Clinical Cases in Eye care provides real-world case examples to illustrate the current scope of primary eye care practice. Over 120 clinical cases help readers gain familiarity with frequently seen scenarios as they would unfold in a typical setting. This case collection is a useful teaching and learning tool for instructors, students and clinicians